Eosinophil-Specific Granules in Tumor Cell Cytoplasm: Unusual Ultrastructural Findings in a Case of Diffuse-Type Gastric Carcinoma. (August 2015) - Caruso, Rosario Alberto; Branca, Giovanni; Fedele, Francesco; Parisi, Antonino; Finocchiaro, Giuseppe; Ieni, Antonio; Rigoli, Luciana
Abstract A case of desmoplastic variant of diffuse-type gastric carcinoma in a 72-year-old woman is reported. Microscopic findings included poorly cohesive tumor cells, resembling mononuclear inflammatory cells, prominent diffuse desmoplasia, and tumor-associated tissue eosinophilia. Electron microscopy confirmed the undifferentiated phenotype of tumor cells and disclosed activated eosinophils in the tumor stroma. Eosinophil-specific granules were found either free in the tumor stroma or within the cytoplasm of some tumor cells. Electron microscopy provided also circumstantial evidence of phagocytosis of apoptotic eosinophils by tumor cells. Extracellular, membrane-bound, eosinophil-specific granules have been long recognized in tissues associated with eosinophilia, including allergic diseases, inflammatory responses to helminths, and in stroma of some neoplasms. Our ultrastructural study now extends these findings and provides additional morphological evidence of eosinophil-specific granules within the cytoplasm of gastric carcinoma cells.